A comparison of dry rolled and steam rolled sorghum grain - Smith, E.F.; Richardson, D.; Koch, B.A.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Good to choice quality yearling Hereford heifers originating near Fort Davis, Texas, were used in the trial. They had been on bluestem pasture prior to the test and were allotted to treatments on the basis of prior treatment and weight. The two lots were fed in an identical manner except one lot received dry rolled sorghum grain (resembling cracked grain, as rollers were set to crack rather than roll the grain) and the other lot received steam rolled grain. Some difficulty was encountered in removing sufficient moisture from the steam rolled grain after rolling to prevent it from heating.
Keywords: Beef; Dry rolled sorghum; Steam rolled sorghum